1998
DOI: 10.1017/s0022112097007738
|View full text |Cite
|
Sign up to set email alerts
|

Stationary travelling cross-flow mode interactions on a rotating disk

Abstract: This work involves the study of the development of Type 1 stationary and travelling cross-flow modes in the three-dimensional boundary layer over a rotating disk. In order to control the characteristics of the stationary modes, we utilized organized patterns of roughness which were applied to the disk surface. These consisted of ink dots which were equally spaced in the azimuthal direction at a fixed radius in order to enhance particular azimuthal wavenumbers. Logarithmic spiral patterns of dots we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 19 publications
9
45
2
Order By: Relevance
“…are stationary) so that γ i = β, which is consistent with experimental observations discussed in §I. As discussed by Corke & Knasiak, 30 traveling modes can dominate on a highly polished rotating disk and this is also likely to be the case over a highly polished broad rotating cone. However, we are particularly interested in practical engineering applications where highly polished surfaces will not be found.…”
Section: Convective Instabilitysupporting
confidence: 86%
“…are stationary) so that γ i = β, which is consistent with experimental observations discussed in §I. As discussed by Corke & Knasiak, 30 traveling modes can dominate on a highly polished rotating disk and this is also likely to be the case over a highly polished broad rotating cone. However, we are particularly interested in practical engineering applications where highly polished surfaces will not be found.…”
Section: Convective Instabilitysupporting
confidence: 86%
“…However, non-stationary modes (i.e., those where γ 0) can also exist, and some have lower critical Re and higher growth rates than the stationary modes. Corke and co-workers 18,28,29 have shown that non-stationary modes can be important in the transition process over smooth disks, but these tend not to be naturally excited where roughnesses are present. In order to safely predict a stabilization of the boundary layer by surface roughness though, some calculations for travelling modes are included.…”
Section: Travelling Modes and Absolute Instabilitymentioning
confidence: 99%
“…However, the existing studies focussed almost exclusively on the effects of a small number of roughness elements arranged to form certain roughness patterns, the goal being to excite particular disturbance modes to test their characteristics for the development of specific control mechanisms. 9,10,[18][19][20] Work with more general roughness was briefly considered by Zoueshtiagh et al 21 for a rotating disk and, in more depth, by Watanabe et al 22 Zoueshtiagh et al 21 documented a short set of experimental data for velocity profiles over quartz-grain roughened disks and these will be revisited here after the presentation of the current results. Watanabe et al 22 studied uniformly distributed roughness on a rotating cone.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies have been performed to reveal the similarities in the stability characteristics across the entire BEK class (see, for example, the theoretical and experimental studies discussed in papers [9][10][11][12][13][14] for the Bödewadt layer; papers [15,16] for the Ekman layer; and papers [17][18][19][20] for the von Kármán flow). These studies have shown the existence of two main flow instability mechanisms, commonly referred to as the Type I and the Type II modes.…”
Section: Introductionmentioning
confidence: 99%